Some Invariant Solutions of Two-Dimensional Elastodynamics in Linear Homogeneous Isotropic Materials (Advances in Applied Mathematics and Mechanics, 2013)
Invariant solutions of two-dimensional elastodynamics inlinear homogeneous isotropic materials are considered viathe group theoretical method. The second order partialdifferential equations of elastodynamics are reduced toordinary differential equations under the infinitesimaloperators. Three invariant solutions are constructed. Theirgraphical figures are presented and physical meanings areelucidated in some cases.